2016
DOI: 10.1038/srep21897
|View full text |Cite
|
Sign up to set email alerts
|

Improved p-type conductivity in Al-rich AlGaN using multidimensional Mg-doped superlattices

Abstract: A novel multidimensional Mg-doped superlattice (SL) is proposed to enhance vertical hole conductivity in conventional Mg-doped AlGaN SL which generally suffers from large potential barrier for holes. Electronic structure calculations within the first-principle theoretical framework indicate that the densities of states (DOS) of the valence band nearby the Fermi level are more delocalized along the c-axis than that in conventional SL, and the potential barrier significantly decreases. Hole concentration is grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 47 publications
1
36
0
Order By: Relevance
“…Technological advances in crystal growth showed that problems like the solubility limit, hydrogen passivation, and high defect ionization energies, hampering p-type conduction, can be overcome to some extent. [5][6][7] Doping by ion implantation offers several advantages over doping during growth especially for selective area doping as reported by Tadjer et al 8 Furthermore, the present generation of "white" LEDs, using a phosphor, suffers from efficiency problems. Recently, Lim et al proposed a phosphor-free white LED based on threedimensional gallium nitride structures.…”
mentioning
confidence: 99%
“…Technological advances in crystal growth showed that problems like the solubility limit, hydrogen passivation, and high defect ionization energies, hampering p-type conduction, can be overcome to some extent. [5][6][7] Doping by ion implantation offers several advantages over doping during growth especially for selective area doping as reported by Tadjer et al 8 Furthermore, the present generation of "white" LEDs, using a phosphor, suffers from efficiency problems. Recently, Lim et al proposed a phosphor-free white LED based on threedimensional gallium nitride structures.…”
mentioning
confidence: 99%
“…In this way, the Mg acceptor activation energy can significantly be reduced to 0.26 eV, very close to that of GaN, in (AlN) 5 /(GaN) 1 SL by Mg Ga δ-doping 1 . Recently, improved p-type conductivity was achieved in multidimensional Al 0.63 Ga 0.37 N/Al 0.51 Ga 0.49 N SLs 33 . In this work, we use Mg Ga δ doping in (AlN) m /(GaN) n SLs to study Mg acceptor activation energy, aiming to find a proper way to minimize it in high Al-content AlGaN.…”
mentioning
confidence: 99%
“…To improve the free hole concentration in high-Al content AlGaN materials, researchers have developed the approach of polarization doping [6][7][8][9][10] for the purpose of enhancing electrical conductivity. By linearly grading the Al composition of AlGaN, the polarization bound charge spreads to a 3D form and induces the formation of a mobile 3D carrier gas of the opposite charge, resulting in an increased carrier concentration [11][12][13][14][15] over impurity doping.…”
Section: Introductionmentioning
confidence: 99%